Nelayan Rumpon (Rompo) di Desa Holimombo Jaya Kecamatan Pasarwajo Kabupaten Buton - Darmin .; Nasruddin Suyuti; La Janu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
This study aims at finding and describing the activities of rumpon fishermen in the village of Holimombo Jaya, Pasarwajo Subdistrict, Buton Regency. This research uses the functional theory of Bronislaw Malinowski that all human activities are actually to satisfy a series of needs of human beings instincts associated with their lives. Ethnographic method is the method used in this research that is using participant observation technique and indepth interview, then the data is analyzed to be described as research report. The results show that the activities of fishermen of the clumps of fishermen were conducted all the time, both in the east monsoon season (musino cimburu) of the west season (musino bhara), both day and night. Therefore, rumpon fishermen need the sacrifice of time, energy and material are not small. First, prepare the raw material for FADs; second, to make FADs; third, prepare equipment such as ship (kapala), machine (masina), newspaper (mina) and jaring (jare); fourth, take the catch; fifth, the distribution of catch and the sixth, the allocation of production. Keywords: activities, rumpon fishermen